A meta-analytical comparison of atenolol with angiotensin-converting enzyme inhibitors on arterial stiffness, peripheral blood pressure and heart rate in hypertensive patients. (4th July 2017) - Xie, Hong; Luo, Gaoqing; Zheng, Yong; Peng, Feng; Xie, Liangdi
ABSTRACT: Objectives : This meta-analysis of randomized parallel controlled trials was designed to compare the efficacy of atenolol with angiotensin-converting enzyme inhibitors (ACEIs) in changing pulse wave velocity (PWV), peripheral blood pressure and heart rate (HR) among patients with essential hypertension. Methods : This study was conducted according to the PRISMA guideline. Data collection was independently completed by two investigators. Statistical analyses were completed by Stata software (v12.0). Results : Eight clinical trials were meta-analyzed in this study. Overall changes in PWV (weighted mean difference or WMD = 0.068, 95% confidence interval or CI: −0.487 to –0.623, P = 0.811) and peripheral systolic blood pressure (PSBP) (WMD = −1.281 mmHg, 95% CI: −6.936 to 4.375, P = 0.657) did not differ significantly between atenolol and ACEIs treatment. Relative to ACEIs, atenolol had a more favorable impact on peripheral diastolic blood pressure (PDBP) (WMD = −1.912 mmHg, 95% CI: −3.732 to −0.091, P = 0.040) and HR (WMD = −9.23 bpm, 95% CI: −12.53 to −5.93, P < 0.001). In stratified analyses, particularly by follow-up period, atenolol was observed to be superior over ACEIs within early 3-month treatment in PSBP (WMD = −4.097 mmHg, 95% CI: −6.589 to −1.605, P = 0.001), PDBP (WMD = −6.802 mmHg, 95% CI: −8.517 to −5.087, P < 0.001) and HR (WMD = −14.242 bpm, 95% CI: −16.427 to −12.058, P = 0.028), without heterogeneity ( I 2 = 0.0%). There were low probabilities of publication bias for all comparisons. Conclusions : Our findings demonstrate that atenolol and ACEIs were equally effective in reducing PWV and PSBP, while atenolol was superior over ACEIs in improving PDBP and HR, especially within short-term treatment.